Chatter avoidance in cutting highly flexible workpieces. Issue 1 (2017) - Stepan, Gabor; Kiss, Adam K.; Ghalamchi, Behnam; Sopanen, Jussi; Bachrathy, Daniel
Abstract: Robust stability analysis of turning is presented for flexible workpiece. The varying dynamic properties due to the material removal process is modelled by means of finite element method. The Frequency Response Function is traced along tool position. The results show significant change in the natural frequency and modal stiffness, which have strong influence on regenerative chatter vibration. Different sections of the multiple-parameter stability lobe diagram are presented and validated with experimental results. The robust stable parameters of initial diameter and chip width are identified for which no chatter occurs along the whole tool position for any spindle speed.